Cortical and subcortical atrophy in Alzheimer disease: parallel atrophy of thalamus and hippocampus - Štěpán-Buksakowska, Irena; Szabó, Nikoletta; Hořínek, Daniel; Tóth, Eszter; Hort, Jakub; Warner, Joshua; Charvát, František; Vécsei, László; Roček, Miloslav; Kincses, Zsigmond T (Alzheimer disease and associated disorders, 2014)
Brain atrophy is a key imaging hallmark of Alzheimer disease (AD). In this study, we carried out an integrative evaluation of AD-related atrophy. Twelve patients with AD and 13 healthy controls were enrolled. We conducted a cross-sectional analysis of total brain tissue volumes with SIENAX. Localized gray matter atrophy was identified with optimized voxel-wise morphometry (FSL-VBM), and subcortical atrophy was evaluated by active shape model implemented in FMRIB's Integrated Registration Segmentation Toolkit. SIENAX analysis demonstrated total brain atrophy in AD patients; voxel-based morphometry analysis showed atrophy in the bilateral mediotemporal regions and in the posterior brain regions. In addition, regarding the diminished volumes of thalami and hippocampi in AD patients, subsequent vertex analysis of the segmented structures indicated shrinkage of the bilateral anterior thalami and the left medial hippocampus. Interestingly, the volume of the thalami and hippocampi were highly correlated with the volume of the thalami and amygdalae on both sides in AD patients, but not in healthy controls. This complex structural information proved useful in the detailed interpretation of AD-related neurodegenerative process, as the multilevel approach showed both global and local atrophy on cortical and subcortical levels. Most importantly, our results raise the possibility that subcortical structure atrophy is not independent in AD patients.
Keywords: senioři; interpretace obrazu počítačem; Cross-Sectional Studies; Thalamus; senioři nad 80 let; Male; hipokampus; Middle Aged; mužské pohlaví; Alzheimer Disease; průřezové studie; atrofie; magnetická rezonanční tomografie; Aged, 80 and over; Magnetic Resonance Imaging; mozková kůra; ženské pohlaví; Humans; Cerebral Cortex; lidé středního věku; Alzheimerova nemoc; Image Interpretation, Computer-Assisted; Female; thalamus; Aged; lidé; Atrophy; Hippocampus